Reliability of telemetric electromyography and near-infrared spectroscopy during high-intensity resistance exercise - Scott, B. R.; Slattery, K. M.; Sculley, D. V.; Lockie, R. G.; Dascombe, B. J. (Journal of Electromyography and Kinesiology, 2014)
This study quantified the inter- and intra-test reliability of telemetric surface electromyography (EMG) and near infrared spectroscopy (NIRS) during resistance exercise. Twelve well-trained young men performed high-intensity back squat exercise (12 sets at 70-90% 1-repetition maximum) on two occasions, during which EMG and NIRS continuously monitored muscle activation and oxygenation of the thigh muscles. Intra-test reliability for EMG and NIRS variables was generally higher than inter-test reliability. EMG median frequency variables were generally more reliable than amplitude-based variables. The reliability of EMG measures was not related to the intensity or number of repetitions performed during the set. No notable differences were evident in the reliability of EMG between different agonist muscles. NIRS-derived measures of oxyhaemoglobin, deoxyhaemoglobin and tissue saturation index were generally more reliable during single-repetition sets than multiple-repetition sets at the same intensity. Tissue saturation index was the most reliable NIRS variable. Although the reliability of the EMG and NIRS measures varied across the exercise protocol, the precise causes of this variability are not yet understood. However, it is likely that biological variation during multi-joint isotonic resistance exercise may account for some of the variation in the observed results.